1988
DOI: 10.1079/bjn19880130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starches of low digestibility on the rat caecal microflora

Abstract: 1. Male Sprague-Dawley rats were fed on either a purified, fibre-free diet or a diet in which half the maize starch was replaced with uncooked amylomaize or potato starch (equivalent to 100 or 200 g amylase-resistant starch (ARS)/kg diet respectively). Changes in short-chain fatty acids (SCFA), pH, ammonia and a number of bacterial variables in caecal contents were then assessed.2. Both ARS supplements decreased caecal content pH by approximately 1–2 units, with an associated reduction in ammonia concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 24 publications
3
15
1
Order By: Relevance
“…Modifications other than SCFA production have been observed in the large intestine of rats fed amylomaize starch including a significant decreased in bacterial activities of nitro-and azoreductase and [3-glucuronidase (Mallett et al, 1988) and altered bile acid bacterial transformation (Andrieux et al, 1989). Similar observations have also been reported for various other poorly digestible carbohydrates and have been related to the decrease in caecal pH in CV rats fed these carbohydrates and to a modification of the bacterial population in the large intestine (Andrieux et al, 1989).…”
Section: Discussionsupporting
confidence: 69%
“…Modifications other than SCFA production have been observed in the large intestine of rats fed amylomaize starch including a significant decreased in bacterial activities of nitro-and azoreductase and [3-glucuronidase (Mallett et al, 1988) and altered bile acid bacterial transformation (Andrieux et al, 1989). Similar observations have also been reported for various other poorly digestible carbohydrates and have been related to the decrease in caecal pH in CV rats fed these carbohydrates and to a modification of the bacterial population in the large intestine (Andrieux et al, 1989).…”
Section: Discussionsupporting
confidence: 69%
“…The glycolytic activities (b-glucosidase, b-glucuronidase and b-galactosidase) were assayed under aerobic conditions according to Mallet et al, 20 using speci®c substrates (galactoside, glucuronide or glucoside) linked with p-nitrophenol. The release of p-nitrophenol from the p-nitrophenylglycoside was evaluated by spectrophotometry at 400 nm.…”
Section: Analysis Of Bacterial Enzymesmentioning
confidence: 99%
“…Mallett et al (11) reported that the decrease in cecal branched-chain SCFA was associated with the reduction in cecal cancer-related enzyme activities in rats fed a low-digestible starch diet. Such changes may be due to the suppression of putrefactive intestinal bacteria and are desirable in preventing colon cancer .…”
Section: Effect Of Fos On Constipationmentioning
confidence: 99%